Improving the ecological validity of isokinetic knee tests at different hip angles: reciprocal concentric-eccentric movements as a suitable alternative for discrete tests - Alt, T.; Nolte, K.; Horn, D.; Modenbach, D.; Jaitner, T.; Knicker, A. J. (Research in Sports Medicine, 2023)
Isokinetic knee tests mostly evaluate reciprocal concentric-concentric flexor-extensor movements in a seated position. Discrete tests generate higher moments, but time requirements impede their widespread implementation. This study examined if hip angle (flexed vs. extended) and test modality (discrete vs. reciprocal) affect camera-based data (100 fps). Sixteen healthy males performed concentric (con) and eccentric (ecc) isokinetic knee flexor (H) and extensor (Q) movements (60°/s). Peak moments and contractional work of discrete and reciprocal tests (QconQecc, HconHecc) strongly correlated for extended (Q:91%=R2=71%; H:95%=R2=87%) and flexed hip (Q:88%=R2=70%; H:81%=R2=75%) without significant differences (p>0.05) between test modalities. Discrete and "traditional" seated QconHcon-tests revealed substantially lower correlations for extended (Q:44%=R2=43%; H:55%=R2=54%) and flexed hip (Q:81%=R2=77%; H:48%=R2=47%). Although most mean values did not significantly differ, moderate correlations were predominant and the respective limits of agreement demonstrated considerable effects of hip angle and test modality. These insights assist practitioners in interpreting isokinetic data of different test procedures. If time constraints prevent discrete knee tests (gold standard), concentric-eccentric movements provide highly correlated outcomes, independent of the hip angle.